2017
DOI: 10.1111/prd.12160
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial modulators of bone remodeling in the periodontal pocket

Abstract: The signaling network involved in the pathogenesis of periodontal disease is not yet fully understood. This review aims to describe possible mechanisms through which the bacterial modulators may be linked directly or indirectly to the process of alveolar bone loss in periodontitis. From the late 1970s to present, new paradigm shifts have been developed regarding our understanding of pathological bone remodeling in periodontal disease. Upcoming evidence suggests that in periodontal disease the local immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 94 publications
0
23
0
Order By: Relevance
“…The suppressed host immune response leads to a local immune response, which can enable periodontopathic bacteria to evade the host immune system. Furthermore, host immunological cells activated by bacteria produce various pro‐inflammatory mediators, eventually leading to periodontal tissues breakdown (Bosshardt, ; Henderson & Kaiser, ).…”
Section: Introductionmentioning
confidence: 99%
“…The suppressed host immune response leads to a local immune response, which can enable periodontopathic bacteria to evade the host immune system. Furthermore, host immunological cells activated by bacteria produce various pro‐inflammatory mediators, eventually leading to periodontal tissues breakdown (Bosshardt, ; Henderson & Kaiser, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Basic National Health Research Department (RISKESDAS) reported the prevalence of periodontal disease as having reached 96.58 %, thereby representing the second most common oral and dental condition in Indonesia [2][3][4]. Numerous previous studies relating to dentistry have analyzed the relationship between bacterial activity and inflammation resulting from periodontal disease which lead to problematic alveolar bone defects [5]. To overcome these defects, numerous techniques such as hydroxyapatite [6,7] or Carbonate-apatite bone graft [8] have been developed to stimulate and enhance the regeneration of alveolar bone.…”
Section: Introductionmentioning
confidence: 99%
“…In periodontitis, an intensified host inflammatory response against subgingival biofilms, consisting primarily of inflammophilic gram-negative species, causes the destruction of gingival tissue and alveolar bone (for reviews see refs. [4,5]) In this excessive inflammation neutrophils produce disproportionate amounts of reactive oxygen species (ROS) that take part in the tissue destruction (for review, see ref. [6]).…”
Section: Introductionmentioning
confidence: 99%